Transformasi Ushul Al-Fiqh kedalam Ushul An-Nahwi: Sejarah dan adopsi - Mubarok, Muhammad Resa; Harahap, Zulfadhli (Maliki Interdisciplinary Journal, 2024)
The history and development of Ushul Nahwu, which is the science of Arabic grammar. Ushul Nahwu is not only concerned with grammar itself, but also with the origins of the Arabic language and how it has developed over time. The science of Ushul Nahwu and Nahwu itself are closely intertwined, where Nahwu is the practical application of the rules studied in Ushul Nahwu. In the second century Hijri, figures such as al-Khalil bin Ahmad and Sibawaih played an important role in establishing the basics of Nahwu. Meanwhile, Ushul Nahwi as a methodological science for compiling new Nahwu rules was formulated in the third century Hijri by Ibn al-Sarraj. Ushul Nahwu adopts two main aspects: methodology and substance. In methodology, Ushul Nahwu uses legal sources such as the Qur'an, Hadith, Ijma', and Qiyas, as well as methods of reasoning such as istishab and qiyas. Scholars such as Ibn Jinni, al-Anbari, and as-Suyuti made important contributions to the development of Ushul Nahwu by compiling rules based on principles such as sama', qiyas, ijma', and istishab. They viewed Ushul Nahwu as a flower garden with a variety of thoughts that dug up arguments to support their theories.